Modelling and Analysis of Continuous Stirred Tank Reactor through Simulation - Anbu, S.; Senthilkumar, M. (Asian Journal of Engineering and Applied Technology, 2018)
A Continuous Stirred Tank Reactor (CSTR) finds its application in many chemical and petrochemical process industries. CSTRs exhibit reasonably high non-linear behaviour. CSTRs are open systems, where thematerial is free to enter or exit the system, which operates on a steady-state basis, where the conditions in the reactor don’t change with time. The reactants are continuously introduced into the reactor, while products are continuously removed.CSTRs are very well mixed, so the contents have relatively uniform properties such as temperature, density, etc. throughout. Further, the majority of chemical reactors are Multi-Input Multi-Output (MIMO) systems, which again develop a high degree of complexity in the development of control systems due to the process interactions, dead time and process nonlinearities. The control of CSTR throws a challenge to the control engineers to design a well-suited controller for its smooth operation. To develop effective control strategies, the behaviour of the reactor needs to be studied. Generally, CSTR behaves differently at different operating regimes. This article attempted to make a comprehensive study on the CSTR through modeling and simulation of the open-loop behaviour using MATLAB.